2015
DOI: 10.3349/ymj.2015.56.6.1694
|View full text |Cite
|
Sign up to set email alerts
|

Community Integration and Quality of Life in Aphasia after Stroke

Abstract: PurposeTo examine community integration and contributing factors in people with aphasia (PWA) following stroke and to investigate the relationship between community integration and quality of life (QOL).Materials and MethodsThirty PWA and 42 age-and education-matched control subjects were involved. Main variables were as follows: socioeconomic status, mobility, and activity of daily living (ADL) (Modified Barthel Index), language function [Frenchay Aphasia Screening Test (FAST)], depression [Geriatric Depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
58
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 33 publications
8
58
1
5
Order By: Relevance
“…Overall, the studies indicated a greatly reduced productivity level, with few working-age participants returning to paid employment. In a study on a moderate level of evidence, it was found that PWA spent less time on education than individuals without aphasia 20 . The data from an additional study with a low level of evidence indicated that five out of twelve PWA noted moderate or severe limitations in informal education 25 .…”
Section: Education and Employmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the studies indicated a greatly reduced productivity level, with few working-age participants returning to paid employment. In a study on a moderate level of evidence, it was found that PWA spent less time on education than individuals without aphasia 20 . The data from an additional study with a low level of evidence indicated that five out of twelve PWA noted moderate or severe limitations in informal education 25 .…”
Section: Education and Employmentmentioning
confidence: 99%
“…Two studies on a moderate to high level of evidence used the Productivity subscale of the CIQ, with both finding limitations in productivity 20,21 . Attention was given to return to work 13,24,28,29 and the ability to participate in work activities 24,25 .…”
Section: Education and Employmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A pesar de esto los pacientes con trastorno cognitivo y de la comunicación son excluidos de los estudios, lo que lleva a una carencia de resultados objetivos en esta población, que hace que el enfoque en algunos programas de rehabilitación no sea el adecuado y solamente se trate la alteración del lenguaje y comunicación y no el impacto real de la afasia para lograr una integración a la comunidad que permita mejorar la calidad de vida [38][39][40] .…”
Section: Escala De Calidad De Vida De Ictus Y Afasia Saqol-39unclassified
“…For example, Australian social housing developments have traditionally been located in poorer neighbourhoods and on the outskirts of a community (Jackson, 2008;Wiesel, 2011). With research to suggest that community participation and social integration improves quality of life (Lee et al, 2015;McGarrigle and Layte, 2015), a small number of social housing dwellings have recently been constructed in more central locations. However, being physically located within a community does not necessarily result in community participation, given that "relationships are not always spontaneously formed" (Winkler et al, 2011, p. 161).…”
Section: Introductionmentioning
confidence: 99%